Wild Origin Material - The Sine Qua Non of Botanic Garden Collections? - Cullen, James (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2004)
Botanic gardens make great claims for their content of 'wild origin material' for use in research, education and conservation. But the material included under this heading is very diverse in its nature and origin, covering a broad spectrum of histories. Various types of wild origin material are distinguished, and the effects of these distinctions on botanic gardens record systems briefly considered.